Bariatric Roux-En-Y Gastric Bypass Surgery: Adipocyte Proteins Involved in Increased Bone Remodeling in Humans - Biagioni, Maria Fernanda G [UNESP]; Mendes, Adriana L [UNESP]; Nogueira, Célia Regina [UNESP]; Leite, Celso V [UNESP]; Gollino, Loraine [UNESP]; Mazeto, Gláucia Mfs [UNESP] (Springer Nature, 2017)
Purpose: Bariatric surgery has been associated with bone remodeling changes. The action of adipokines on the expression of receptor activator of nuclear factor kappa β ligand (RANKL) and osteoprotegerin (OPG) and on an increase in sclerostin could be related to these changes. Materials and Methods: This study aimed to assess the repercussions of weight loss, fat mass (FM), and fat-free mass (FFM) loss and biochemical and hormonal changes on bone remodeling markers after Roux-en-Y gastric bypass (RYGB). Anthropometric data, parathyroid hormone (PTH), bone-specific alkaline phosphatase (BSAP), collagen type 1 C-telopeptide (CTX), 25-hydroxy vitamin D (25-OH-VitD), leptin, adiponectin, RANKL, OPG, and sclerostin of 30 menstruating women were measured preoperatively (Pre), and 3, 12, and 24 months (m) after RYGB. Results: Leptin (34.4 (14.7; 51.9) vs. 22.5 (1.9; 52.7) ng/mL) and OPG (3.6 (1.1; 11.5) vs. 3.4 (1.5; 6) pmol/L) decreased, and adiponectin (7.4 (1.7; 18.4) vs. 13.8 (3.0; 34.6) μg/mL), CTX (0.2 (0.1; 2.2) vs. 0.6 (0.4; 6.0) ng/mL), RANKL (0.1 (0.0; 0.5) vs. 0.3 (0.0; 2.0) pmol/L), and sclerostin (21.7 (3.2; 75.1) vs. 34.8 (6.4; 80.5) pmol/L) increased after 3 m. BSAP increased after 12 m (10.1 (5.4; 18.9) vs. 13.9 (6.9; 30.2) μg/mL) (p < 0.005). CTX correlated positively with adiponectin at 24 m and inversely with leptin Pre; OPG at 3 m; weight, FM, FFM, and leptin at 24 m. RANKL correlated directly with weight at 3 m. Sclerostin correlated inversely with weight Pre and FM at 3 m. BSAP correlated negatively with 25-OH-VitD at 12 m, and positively with PTH at 24 m. Conclusions: RYGB induced weight loss, and biochemical, hormonal, and body composition changes are associated with higher bone remodeling.
Keywords: Bariatric surgery; Biomarkers; Bone remodeling; Cytokines; Wnt/β-catenin/LRPs